Regulation of Smad4 sumoylation and transforming growth factor-β signaling by protein inhibitor of activated STAT1 - Liang, Min; Melchior, Frauke; Feng, Xin-Hua; Lin, Xia (The journal of biological chemistry, 2004)
The tumor suppressor, Smad4/DPC4, is a common signal transducer in transforming growth factor-β (TGF-β) signaling. In this study, we demonstrated that the protein inhibitor of activated STAT1 (PIAS1) regulates the signaling potential of Smad4 through a sumoylation-dependent mechanism. PIAS1 was shown to be an E3 ligase for Smad4 sumoylation in vitro and in vivo. PIAS1 physically interacted with Smad4 in a TGF-β-inducible manner. A minimal SUMO E3 ligase domain and Smad4-binding domain were defined on PIAS1 protein. The RING finger domain of PIAS1 was essential for its E3 ligase function. Although PIAS1 enhanced the Smad4-dependent transcriptional activation of TGF-β signaling, a mutant lacking the RING domain inhibited the sumoylation of Smad4 in a dominant negative manner and, as a result, abolished the transcriptional response of TGF-β. These data demonstrate that PIAS1 protein positively modulates TGF-β responses as a SUMO E3 ligase for Smad4.
Gesehen am 05.09.2023